Development and Validation of a Liquid Chromatographic Method for the Simultaneous Analysis of Six Protease Inhibitors Using a Polymer Column (The East and Central African Journal of Pharmaceutical Sciences, 2018)
A liquid chromatographic method for the simultaneous determination of six human immunodeficiency virus (HIV) protease inhibitors, indinavir, saquinavir, ritonavir, amprenavir, nelfinavir and lopinavir, was developed and validated. Optimal separation was achieved on a PLRP-S 100 Å, 250 x 4.6 mm I.D. column maintained at 60 °C, a mobile phase consisting of tetrahydrofuran-potassium phosphate buffer (0.1M, pH 5.0)-tetrabutylammonium hydrogen sulphate (0.1M, pH 5.0)-water (35:30:10:25 %v/v) at a flow rate of 1.0 ml/min, with ultraviolet detection at 254 nm. The method was found to be linear over the ranges investigated with r2 values of 0.9997-0.9915 for the six drugs. The limit of quantitation for the six drugs was 0.16 to 5.12 µg, while the limit of detection was 0.08 to 2.12 µg. The intra-day and interday precision was within the ranges of 0.39 to 1.14% and 0.55 to 1.46%, respectively.
Keywords: Protease inhibitors; liquid chromatography; poly(styrene-divinylbenzene); method development; method validation.